Analysis of specialist doctors' behavior towards SGLT2 inhibitors prescription in Indonesia: A qualitative study - Cokro, Fonny; Sauriasari, Rani; Tahapary, Dicky L.; Setiawan, Heri; Martha, Evi (Narra Sains Indonesia, 2025)
Sodium-glucose cotransporter-2 inhibitors (SGLT2is) have a broad range of clinical indications and are recommended by various guidelines for the management of diabetes, heart failure, and chronic kidney disease. However, prescribing rates for these agents are suboptimal towards various intended indications in many countries, including Indonesia. The aim of this study was to analyze the prescribing practices of SGLT2is among endocrinologists, cardiologists, and nephrologists in Indonesia. A qualitative method was utilized to provide a comprehensive understanding of this phenomenon. Semi-structured online interviews were performed with 18 participants, comprising seven specialized doctors as primary informants; eight key informants representing pharmacies, governmental bodies, and pharmaceutical marketing representatives; and three patients as supplementary informants. Furthermore, closed observations of two specialist doctors were undertaken as an additional data collection method. Informants were recruited using criterion and snowball sampling methods. The Theoretical Domains Framework was used as an interview guide; all interviews were audio visual-recorded, transcribed verbatim, and subsequently analyzed for thematic content with NVivo version 12. Seven themes emerged concerning the prescribing behavior of SGLT2is: socioeconomic status, therapeutic rationality, utilization barriers, utilization optimization, the urge to prescribe, therapeutic expectations and targets, and aspects of the health system and ethical considerations. Most informants possessed favorable perspectives regarding using SGLT2is when prescribed appropriately, yet specific elements necessitate enhancement to refine therapeutic justification, including initiatives to incorporate SGLT2is into the national formulary.